Protection of Advocates Immunity Rights in The Criminal Code: Between Legal Certainty and Justice - Anderson Subri; Adnan Hamid; Supaphorn Akkapin (Journal Evidence Of Law, 2025)
The protection of advocates’ immunity rights is a fundamental aspect of ensuring their role as independent and equal law enforcers within the criminal justice system. In Indonesia, advocate immunity is regulated under Article 16 of Law No. 18 of 2003 on Advocates and was further interpreted by the Constitutional Court Decision No. 26/PUU-IX/2013 to extend beyond courtroom proceedings. However, the emergence of the Criminal Code (KUHP) raises new debates regarding the explicit recognition and operational guarantees of such rights. This study aims to analyze the normative position of advocate immunity in the KUHP and assess its implications for legal certainty and the pursuit of justice. Employing a normative legal approach and comparative analysis with other legal systems, the research finds that the current lack of clear and explicit provisions protecting advocates’ immunity in the KUHP is a notable deficiency. This legal gap may weaken the position of advocates and expose them to risks of criminalization in the performance of their professional duties. Therefore, this paper recommends a clearer normative formulation that ensures adequate protection for advocates while upholding a balanced realization of legal certainty and substantive justice in Indonesia’s criminal justice system.